A Study On Media In Listening Comprehension At Second Year Students Of English Language Education Program - Erythrina Crista Wijayanti (EDUCAFL : Journal of Education of English as Foreign Language, 2021)
Listening comprehension is one of the important aspects in mastering English. In listening, students need to comprehend what they are listening to. During the listening process, problems may hinder their understanding for arriving at succesful listening comprehension. These problems might be coped with the use of media in order to aid their listening. Thus, this study was aimed to find out students’ opinion about the media that helped them in understanding Listening Comprehension materials and their reasons in choosing the media.This study used descriptive survey. Questionnaire and interview were developed based on media types, micro and macro skills of listening and listening comprehension process theories. The questionnaire was distributed to 90 Second Year Students of English Language Education Program. The data from the questionnaire were analyzed quantitatively to find out the students’ perception, while the data from the interview were analyzed qualitatively to describe the students’ reasons in choosing the media.There were two findings in this research. First, media that helped the students in understanding Listening Comprehension materials and second, the students’ reasons in choosing the media seen from two aspects: (1) how the media helped the students to master the micro and macro skill of listening and (2) how the media helped the students to understand the listening comprehension process. The first finding showed 74.13% of students selected audio visual media that helped them in understanding Listening Comprehension, while 25.175% and 0.695% of them preferred audio and visual media respectively. The second finding showed to improve to the macro skills of listening, 61.73% of the students argued that they were helped by audio visual media, while 38.26% of them were helped by audio media. On the other hand, 53.35% of the students aired their opinion that their micro skills of listening were improved through the use of audio visual media and 46.64% of them stated that they are helped with the audio media use. Film, television, video, computer, gadget, games and song accommodated all of the eight listening comprehension processes. Therefore, the researcher suggests that the teacher should use audio media to help the students in mastering the micro skill of listening and audio visual media to assist the students in understanding the macro skill of listening. In addition, film, television, video, computer, gadget, games and song should be used to support the students in comprehending the listening comprehension process.